Claudin-4 localization in epithelial ovarian cancer. Issue 10 (October 2022) - Neville, Margaret C.; Webb, Patricia G.; Baumgartner, Heidi K.; Bitler, Benjamin G.
Abstract: Claudin-4, a protein with the structure of classic claudins most often found in cell-cell junctions, is frequently overexpressed in epithelial cancers where its localization has not been studied. In this study we aimed to find out where this membrane protein is localized in an ovarian tumor model, OVCAR3 cells, that express high levels of the protein. Immunohistochemical studies showed claudin-4 staining in a perinuclear region, at most plasma membranes and in cytoplasmic puncta. Native claudin-4 did not overlap with phosphorylated claudin-4, which was partially located in focal adhesions. Using claudin-4 BioID technology we confirmed that large amounts of claudin-4 are localized to the Golgi compartment, including in dispersed Golgi in cells where claudin-4 is partially knocked down and in dividing cells. Claudin-4 appears to be present in the vicinity of several types of cell-cell junctions, but there is no evidence that it forms tight junctions in these tumor cells. Both claudin-4, the Golgi marker GM130, and the plasma membrane receptor Notch2 were found in dispersed Golgi in dividing cells. This definition of the cellular architecture of claudin-4 should provide a framework for better understanding of the function of claudin-4 in tumor cells and its molecular interactions. Abstract : Claudin-4; Ovarian cancer; Golgi; Endoplasmic reticulum; Endosome; Cell-cell contacts; Plasma membrane proteins; Cell architecture.